PENYELENGGARAAN KARTU PRIBADI DALAM BIMBINGAN DAN KONSELING - WILDAN HALID (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2016)
In this research, the researcher will explain the practical parts, how is the initial process until the next process about conducting personal card especially at school. The personal card is very important so it is very in need to promptly carried out, from a personal card a guider can be identified in all majors, either the guidance or counseling. The counseling process in the school will go well if all of the data about the counselee is complete. The relation of implementation of the personal card is an Islamic Guidance Counseling teacher can easily find out a child or her/his life outside school, what activities outside school, with whom she/he gets along and the important thing is about her/his spiritual level. The conclusion of this reseach was first, the personal card is a list that contains all the aspects from of the circumstances of the child. Second, from this personal card the guider can shove off into all the majors, both for guidance as well as counseling. Third, the data to be quickly retrived, Fourth, the material in the personal card, fifth, facilitate the counseling process.